A COMPARISON OF ABBREVIATED BURN SEVERITY INDEX (ABSI) SCORE WITH R-BAUX SCORE AS A PREDICTOR OF MORTALITY IN BURN PATIENTS - Iustitiati, Melissa Anita Ayu; Beta Subakti Nata’atmadja (Jurnal Rekonstruksi dan Estetik, 2022)
HIGHLIGHTS: 1. The R-Baux Score and ABSI Score can be used as model predictors of death in burn patients at Dr. Soetomo General Academic Hospital.2. There was no significant difference between the R-Baux Score and the ABSI Score as the predictor of mortality in burn patients.   ABSTRACT: Background: Several studies regarding the mortality predictor model in burn patients have been carried out in several cities and countries. However, none have ever happened in Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. This study aims to analyze the R-Baux Score and Abbreviated Burn Severity Index (ABSI) Score as a mortality predictor model in burn patients, which are relevant and useable in services at Dr. Soetomo General Academic Hospital. Methods: This study used quantitative research with a cross-sectional design and retrospective design utilizing secondary data. It was found that 263 patients met the inclusion criteria; with 73 patients died, 60.27% of whom were male, 50% with inhalation trauma, 19.18% were in the age range of 56-65 years old, 24.66% had a burn area of 61-70%, and 35.62% with a full-thickness burn. Results: The results showed that the sensitivity value from the ABSI Score (p<0.001) was 82.19%, with a specificity of 82.11%, a positive predictive value of 63.83%, and a negative predictive value of 92.31%. The R-Baux Score (p<0.001) showed that the sensitivity value obtained was 80.82%, with a specificity of 80.00%, a positive predictive value of 60.83%, and a negative predictive value of 91.57%. Conclusion: There was no significant difference between the R-Baux Score and the ABSI Score as the predictor of mortality in burn (p>0.05). Therefore, both the R-Baux Score and the ABSI Score can be used as model predictors of death in burn patients at Dr. Soetomo General Academic Hospital.